Roadmap for cost-effective, commercially-viable perovskite silicon tandems for the current and future PV market - Sofia, Sarah E.; Wang, Hao; Bruno, Annalisa; Cruz-Campa, Jose Luis; Buonassisi, Tonio; Peters, Ian Marius (Sustainable Energy & Fuels, 2020)
A techno-economic analysis of perovskite-silicon tandem solar modules is presented, outlining the most viable pathway for designing cost-effective, commercially viable tandems. We explore the cost-performance trade-off for silicon bottom cells in perovskite-silicon tandems, and evaluate the potential of using low-cost, lower-efficiency silicon bottom cells, on the basis of levelized cost of electricity (LCOE), compared to the higher-efficiency, higher-cost bottom cells that have been the primary focus of most perovskite-silicon tandem research efforts. We fabricate a cost-effective four-terminal silicon-perovskite tandem using a low-cost multicrystalline bottom cell and calculate the device LCOE. We then extend this analysis by modeling performance and LCOE of similar tandems instead using high-efficiency silicon bottom cells, enabling direct comparison of a low-cost and a high-efficiency tandem. Lastly parametric analyses are performed to more broadly examine the bottom-cell cost-performance trade-off. We show that low-cost silicon, even at the detriment of efficiency, is the more likely path to make perovskite-silicon tandems commercially viable and enable future reductions in LCOE, given both current and near-future silicon technology. We lay out a clear economic motivation for pursuing low-cost silicon bottom cells in perovskite-silicon tandems, showing that they can achieve a 15-20% relative LCOE reduction compared to the single-junction sub-cells. This is a 2-3 times greater relative LCOE reduction compared with using high-efficiency silicon. Furthermore, we show that the advantage of using low-cost silicon bottom cells is robust to and benefits from expected market trends, such as falling system costs and advanced, low-cost manufacturing. This work provides a clear pathway to cost-effective tandems, outlines the benefits for existing multicrystalline silicon manufacturers to investing in tandem development, and points out a clear mismatch between commercial viability and current research efforts.
CRIS-Team Scopus Importer:2022-06-05